Ultrasound biomicroscopic study of sclelotomy sites after implantation of sustained release drug devices. Issue 8 (1st August 2002) - Kunimatsu, S; Fujino, Y; Nagata, Y; Ono, K; Mochizuki, M; Numaga, J; Kawashima, H; Araie, M
Abstract : Background/aims: To evaluate the potential of ultrasound biomicroscopy (UBM) as a tool to study the precise location and changes of sclerotomy sites of the eye with an intraocular drug delivery device. Methods: Eight eyes of six patients (13 sites) who received ganciclovir implants were examined by UBM. Examinations were performed 1–26 months (mean 12.8 months) postoperatively. Serial transverse and radial sections of the anterior ciliary body around the sclerotomy sites were obtained. Results: The ganciclovir implant contour was successfully viewed using an UBM with high reflectivity. Three implants were deviated anteriorly and they were very close to the ciliary body and the lens (anterior deviation), while four implants were deviated posteriorly and away from the lens (posterior deviation). The other six implants were located at the appropriate position as intended. A solitary homogeneous mass with a medium reflectivity around the suture tab was observed at 12 out of 13 sites in seven eyes. Thick membranes extending from sclerotomy sites to the ora serrata were found at two sites in two eyes. Conclusion: UBM is helpful in detecting abnormal manifestations around ganciclovir implants and is a valuable tool to assess the changes of the sclerotomy sites of the sustained released intraocular devices.